Chinese Electric Vehicles (EVs) in Kazakhstan : Public Perceptions and Economic Implications - Kazhibekova, Botagoz (My University, 2025)
This paper aims to explore the integration of Chinese electric vehicles (EVs) into Kazakhstan and analyze the public perceptions of Kazakhstani people about these EVs and their import. The study applies a mixed-method approach: primary data is an online survey among Kazakhstani EV drivers, whereas theoretical and conceptual literature, legal, and government documents served as secondary data. Survey results illustrate a largely positive perception of Chinese EVs in Kazakhstan, highlighting their affordability, technological features, and environmental benefits. Meanwhile, the survey indicates several key challenges, i.e., underdeveloped infrastructure for EV adoption, insufficient government support, and a lack of public awareness about policy incentives. Furthermore, the paper emphasizes the dual nature of Chinese EV integration into Kazakhstan and researches its main implication: is it a new path to economic growth, strengthening Sino- Kazakhstani relations, or a broader reliance on China—currently dominating the global EV market—which may raise its regional power in Central Asia? Beyond the Kazakhstani-focused analysis of the paper, it also discusses broadly the Sino- Kazakhstani strategic economic partnership under the bilateral cooperation and the Belt and Road Initiative (BRI). Additionally, the paper investigates how the BRI infrastructure may facilitate global Chinese EV trade, given Kazakhstan’s role as a transition hub within the initiative. Moreover, it evaluates the contribution of Chinese EV integration together with Kazakhstan’s green transition to the BRI’s goal of sustainable development and, at large, China’s economic leadership. Finally, the study presents insights into Kazakhstan’s efforts to reduce oil and gas dependency through economic diversification and green economy advancement. It also examines key potential opportunities and obstacles of Chinese EV integration for the country and provides policy recommendations related to EV adoption for domestic economic reinforcement.
Keywords: Chinese electric vehicles (EVs), economic cooperation, public perceptions, Sino-Kazakhstani Relations, Belt and Road Initiative (BRI)